2022
DOI: 10.3389/fnut.2022.856089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt (Sodium Chloride) Replacement With Potassium Chloride, High Pressure Processing, and Cold Storage at 4°C on Beef Sausage Volatile Compounds

Abstract: This study aimed to investigate the partial substitution of 0, 25 and 50% sodium chloride (NaCl) by potassium chloride (KCl) coupled with high-pressure processing (HPP) effects on volatile compounds and lipid oxidation of beef sausage at five (0, 3, 7, 14, and 21) different cold storage days (4°C). The odor activity values (OAV) of the various compounds were visualized by heat map analysis. Thiobarbituric acid reactive substances (TBARS) of the samples treated with 100% NaCl and HPP increased by an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…The results showed an increase in their levels compared to the control ones after the treatment. Similar ndings were observed in beef sausage samples pressurized at 100 MPa for ve minutes (Ojangba et al 2022). High concentrations of some hydrocarbons were recorded in pressurized samples compared to unpressurized ones (Ojangba et al 2022).…”
Section: Effect Of Hpp On Color During Cold Storagesupporting
confidence: 80%
See 1 more Smart Citation
“…The results showed an increase in their levels compared to the control ones after the treatment. Similar ndings were observed in beef sausage samples pressurized at 100 MPa for ve minutes (Ojangba et al 2022). High concentrations of some hydrocarbons were recorded in pressurized samples compared to unpressurized ones (Ojangba et al 2022).…”
Section: Effect Of Hpp On Color During Cold Storagesupporting
confidence: 80%
“…Similar ndings were observed in beef sausage samples pressurized at 100 MPa for ve minutes (Ojangba et al 2022). High concentrations of some hydrocarbons were recorded in pressurized samples compared to unpressurized ones (Ojangba et al 2022). It is important to note that hydrocarbons are likely to have minimal impact on odor perception due to their high odor threshold (Ghorbani Gorji et al 2019; Goicoechea and Guillén 2014; Hartvigsen et al 2000;Jacobsen et al 1999).…”
Section: Effect Of Hpp On Color During Cold Storagesupporting
confidence: 80%
“…The multiplicative effect between acidity and saltiness has resulted in using organic acids as flavour enhancers in combination with other low‐sodium salt technologies to reduce sodium addition (Ojangba et al ., 2022). It was found that the obvious bitter taste of fermented sausages made by replacing 50% of salt with potassium chloride disappeared and had a salty enhancing effect after the addition of organic acids such as L‐malic acid, succinic acid, citric acid, and fumaric acid.…”
Section: Introductionmentioning
confidence: 99%